Aerodynamic shape optimization of large-span coal sheds for wind-induced effect mitigation using surrogate models. (15th February 2022) - Qiu, Ye; Yu, Rui; San, Bingbing; Li, Jianhong
Highlights: Surrogate-based optimization procedure for reducing wind-induced effects on coal sheds is developed. Gable type and wind directionality are considered during the optimization design. Applying the RANS modeling to evaluate aerodynamics of large-span coal sheds. Optimal cross-sections of coal sheds exhibit a reasonable aerodynamic performance enhancement. Abstract: Large-span coal sheds commonly used in thermal power plants are particularly vulnerable to wind loads, and the aerodynamic performances are largely affected by their external shapes. The search for the best performing shape through an aerodynamic optimization is still of importance for the mitigation of the design wind loads and responses. This study investigated the possibility of using surrogate models combined with genetic algorithm to carry out the aerodynamic shape optimization of large-span roof structures. The approach is applied to tri-centered coal sheds with closed and open gables, respectively. The shape optimization is numerically performed to minimize the vertical displacement of the shed model while subjecting to one normal and two oblique wind directions, 0°, 30° and 45°. The aerodynamic forces acting on coal sheds immersed in turbulent flow are obtained by the CFD simulation with RSM turbulence model, and the results are validated with wind tunnel tests. Kriging model is used to establish a global mapping between design variables and objective function by conducting a set of CFD and structural static response analyses. Results show that the aerodynamic loads and the optimal geometry are sensitive to the selection of gable types and wind directions. The optimal design presents a reasonable performance improvement compared with the near-optimal and original designs. Several compromised designs are finally provided in order to seek a balance between the effects of wind directionality and construction cost.